A rare Robertsonian translocation rob(14;22) carrier with azoospermia, meiotic defects, and testicular sperm aneuploidy - Sobotka, Vladimir; Vozdova, Miluse; Heracek, Jiri; Rubes, Jiri (Systems biology in reproductive medicine, 2015)
Male infertility is a serious problem in an increasing number of couples. We report an infertile man with non-obstructive azoospermia and karyotype 45,XY,rob(14;22). The immunofluorescence analysis of his testicular tissue using antibodies to SYCP1, SYCP3, HORMAD2, MLH1, and centromeres showed delayed synapsis of the chromosomes involved in the translocation, a varying extent of trivalent asynapsis and its association with sex chromosomes. The mean frequency of meiotic recombination per cell was within the range of normal values. Fluorescence in situ hybridization (FISH) with probes for chromosomes 14 and 22 revealed 5.83% of chromosomally abnormal testicular spermatozoa. FISH with probes for chromosomes X, Y, and 21 showed frequencies of disomic and diploid testicular spermatozoa increased when compared to ejaculated sperm of healthy donors, but comparable with published results for azoospermic patients. PGD by FISH for the translocation and aneuploidy of chromosomes X, Y, 13, 18, and 21 showed a normal chromosomal complement in one out of three analyzed embryos. A healthy carrier girl was born after the embryo transfer. This study shows the benefits of preimplantation genetic diagnosis in a case of a rare Robertsonian translocation carrier with azoospermia and a relatively low frequency of chromosomally unbalanced testicular spermatozoa.
Keywords: Meiosis; aneuploidie; karyotypizace; spermie; meióza; Chromosomes, Human, Pair 14; Spermatozoa; Karyotyping; Chromosomes, Human, Pair 22; lidé; Translocation, Genetic; azoospermie; lidské chromozomy, pár 14; lidské chromozomy, pár 22; Genetic Carrier Screening; Azoospermia; Male; detekce genetických nosičů; mužské pohlaví; translokace genetická; Aneuploidy; Humans